Efforts to Build Employee Work Attachment Through Affective Commitment and Work Discipline - Noermijati; Firdaus, Ema Zahra; Sulastri (Jurnal Entrepreneur dan Entrepreneurship, 2023)
The purpose of this study is to analyze the role of mediation of affective commitment, and work discipline on the effect of job stress on employee work attachment. This research was conducted at the Sugar Factory X in East Java, involving 158 employees. Data were collected using a questionnaire and the results were analyzed using PLS software. The results of this study indicate that job stress does not have a significant effect on work attachment, but affective commitment and work discipline as full mediation on the effect of job stress on work attachment. In testing direct effects on other variables show that, job stress directly influences work discipline and affective commitment, while work discipline and affective commitment directly affect work attachment. This study places affective commitment, and work discipline as a variable for the pillar on the effect of job stress on employee work attachment. The important findings of this study are affective commitment and work discipline act as full mediation variables. That job stress is unable to play a role in efforts to improve employee work attachment unless there is a role in mediation from affective commitment variables and work discipline. The results strengthen the social exchange theory.